Development of Tourism Destination Management in Oro-Oro Ombo Village, Batu City - Pangestuti, Edriana; Susenohaji, Susenohaji; Susilowati, Susilowati; Widia, I Made Dewa; Prayitno, Gunawan; Ridlo, Mahmuddin (Journal of Indonesian Tourism and Development Studies, 2022)
Oro-oro Ombo Village has a strategic geographical and topographical position in Batu City. Located on the southern slopes of Mount Panderman, Batu City, it provides a potential panoramic view of Batu City from the top of the mountain. Many tourist destinations are scattered in this village, mostly on the slopes of Mount Panderman, an icon of Batu City. The obstacle faced is that the village government has not managed the destination properly through the Village-Owned Enterprise (BUMDes), precisely to seize the opportunity, as well as the operational and technical concept of the development. Researchers from the University of Brawijaya (UB) were invited by the Village Head to conduct a series of coordination meetings. The meeting focused on identifying the potential and strategies for its utilization to generate economic benefits. The researchers' initial activity from UB was carried out in 2021 by Doktor Mengabdi (DM) grant, with focus group discussion and observation. The study included identifying potential tourist spots within the Panderman Evergreen Tourism Area and its development as a New Icon of Batu City Tourism, which combines the concepts of recreation, education, conservation, and attraction innovation. The researchers also mapped stakeholders' roles and duties in the development of the Panderman Evergreen Tourism Area. A total of 19 destinations were identified. The development also focused on increasing the rest area to accommodate groups of tourists who use buses, with UB helping develop the Master Plan for the rest area and product creation center. The government of Batu City, State-Owned Forestry Company KPH Malang, Village Government, BUMDes, BUMD of Batu City, and community groups are the relevant stakeholders in mapping the tourist area of Oro-Oro Ombo Village. Research activities by UB is expected to have a positive impact on the development of tourism in Oro-Oro Ombo Village, by developing the master plan. BUMDes Oro-Oro Ombo expects UB to provide continuous assistance in tourism development further in implementing the plan. Keywords: BUMDes, Management, Tourist Destinations.